2005
DOI: 10.1080/10245330400020439
|View full text |Cite
|
Sign up to set email alerts
|

Do alpha deletions influence hydroxyurea response in thalassemia intermedia?

Abstract: Thalassemia intermedia patients show variable phenotypes. Hydroxyurea (HU) may benefit some of the thalassemia intermedia cases (1), however, the parameters influencing the response to HU have not been reported. In this study, the molecular parameters, alpha-globin and beta-globin genotype and the Xmn I polymorphism, were correlated with the HU response. Twenty patients with thalassemia intermedia were given HU (10-20 mg/kg) and responses were evaluated over a one year period. Twelve patients (60%) showed a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
3
18
0
4
Order By: Relevance
“…Hydroxycarbamide may also have a more general role in increasing globin synthesis (Atweh & Loukopoulos, 2001). Large series of TI patients have been reported from Iran (Karimi et al, 2005) and India Panigrahi et al, 2005). The results were impressive, especially in the first study, where most patients were reported to have become transfusion independent.…”
Section: Modulation Of Fetal Haemoglobin Productionmentioning
confidence: 60%
See 1 more Smart Citation
“…Hydroxycarbamide may also have a more general role in increasing globin synthesis (Atweh & Loukopoulos, 2001). Large series of TI patients have been reported from Iran (Karimi et al, 2005) and India Panigrahi et al, 2005). The results were impressive, especially in the first study, where most patients were reported to have become transfusion independent.…”
Section: Modulation Of Fetal Haemoglobin Productionmentioning
confidence: 60%
“…Previous studies from Europe had documented a constant increase of the erythrocyte volume and in HbF, but only a modest effect on total Hb concentration. Co-inheritance of a thalassaemia, the Xmn-1 HBG2 polymorphism (Panigrahi et al, 2005) and the underlying b globin genotype may be predictive of a good response to hydroxycarbamide; Hb E/b thalassaemia patients generally have a good response (Singer et al, 2005). However, one study from Italy reported a decrease in the efficacy of hydroxycarbamide in TI patients after a longterm follow-up (Mancuso et al, 2006).…”
Section: Modulation Of Fetal Haemoglobin Productionmentioning
confidence: 96%
“…50,61,90 Of note, several reports confirm that the effects of hydroxyurea in patients with hemoglobin S/b-thalassemia may be better than those even reported for homozygous hemoglobin S disease, because the synthesized g-chains not only inhibit the sickling process, but they also neutralize the noxious effects of the excess a-chains and cut down on ineffective erythropoiesis. [91][92][93][94][95] Co-inheritance of a-thalassemia was described as a predictor of good response in some studies, 44,77,96 but it was found to have no effect in others. 49,68,85 Homozygosity for the XmnI polymorphism (2158C.…”
Section: Predictors Of Responsementioning
confidence: 99%
“…Clinical experience suggests that induction of fetal hemoglobin production using hydroxycarbamide is associated with increases in total hemoglobin levels of 1 g/dL, a decrease in transfusion demand, and amelioration of certain disease complications like PHT, although a decrease in efficacy on long-term therapy is noted (Panigrahi et al 2005;Karimi et al 2010bKarimi et al ,c, 2011Rigano et al 2010;Taher et al 2010c;Amoozgar et al 2011b). Treatment with hydroxycarbamide may also reduce the incidence of thrombotic events including silent strokes (M Karimi, S Haghpanah, MH Bagheri, et al, unpubl.).…”
Section: Fetal Hemoglobin Inductionmentioning
confidence: 99%